2023
DOI: 10.1039/d3na00313b
|View full text |Cite
|
Sign up to set email alerts
|

Phytofabrication of silver nanoparticles using Averrhoa bilimbi leaf extract for anticancer activity

Abstract: Averrhoa bilimbi leaf extract was successfully utilized as a reducing agent to synthesize silver nanoparticles (AgNPs) in the laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Due to its ability to target specific cells or tumour tissue and function as drug delivery systems, scientists have focused a great deal of emphasis on the use of silver nanoparticles in cancer treatment(Wicki et al, 2015;Khatami et al, 2018). Recent studies have revealed that the silver nanoparticles having a size range of 5-35 nm can mediate the targeted drug delivery as well as can induce programmed cell death (Apoptosis) through mitochondria(Leena et al, 2023).…”
mentioning
confidence: 99%
“…Due to its ability to target specific cells or tumour tissue and function as drug delivery systems, scientists have focused a great deal of emphasis on the use of silver nanoparticles in cancer treatment(Wicki et al, 2015;Khatami et al, 2018). Recent studies have revealed that the silver nanoparticles having a size range of 5-35 nm can mediate the targeted drug delivery as well as can induce programmed cell death (Apoptosis) through mitochondria(Leena et al, 2023).…”
mentioning
confidence: 99%